-Induced Cellulitis in an Immunocompetent Patient With Sickle Cell Disease: A Case Report - Shaher Samrah MBBS, FCCP; Aroob Sweidan MBBS; Abdelwahab Aleshawi MBBS; Mahmoud Ayesh MBBS, MRCP (SAGE Publishing, 2020)
Fungal infections due to Fusarium species are mostly present in immunocompromised and patients with poorly controlled diabetes mellitus. We report a case of lower extremity skin infection caused by Fusarium species in a 61-year-old woman diagnosed with sickle cell disease. Single skin ulceration caused by Fusarium species can result from fungal inoculation into damaged tissue, so any condition that damages the skin can be considered as a risk factor for inoculation. Long-standing sickle cell disease may develop vaso-occlusion in the skin that can produce lower extremity ulcers and myofascial syndromes. The mechanism is not completely characterized, but compromised blood flow, endothelial dysfunction, thrombosis, inflammation, and delayed healing are thought to contribute to locally compromised tissue that may eventually lead to opportunistic infection such as in our case. Other factors contribute to the pathophysiology of lower extremity ulcers such as diabetes mellitus, with the resulting peripheral vascular ischemia causing poor circulation to the lower extremity, and peripheral neuropathy, which can make patients with diabetes unaware of minor trauma leading to the development of skin infections.